1971
DOI: 10.1159/000179908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Haemodialysis on Erythrocyte and Plasma Potassium, Magnesium, Sodium and Calcium

Abstract: Erythrocyte and plasma potassium, magnesium, sodium and calcium were estimated before and after dialysis in 32 studies on 14 patients undergoing recurrent haemodialysis. Predialysis erythrocyte magnesium was raised while sodium and calcium were depressed. Erythrocyte potassium varied depending on the total body potassium status of the patient. During dialysis erythrocyte potassium and magnesium fell but sodium and calcium increased. Changes in erythrocyte water or blood pH did not account for the shift of eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
1

Year Published

1974
1974
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
4
6
1
Order By: Relevance
“…The results indicate that even in this region with the low magnesium content of the drinking water, prolonged dialysis did not deplete erythrocytes or bone of the excess levels of magnesium found in chronic renal failure. This finding over a period of 60 months corresponds with the previously reported results of short-term studies [10,22], In three patients studied, the decreased plasma and ultrafiltrable magnesium levels detected after dialysis returned to normal levels within 4 h. Whether the temporary fall in plasma magnesium concentration induced by dialysis ( fig. 1) is important in provoking an increased response from the para thyroid glands, thus exacerbating any tendency to metabolic bone disease, is not established.…”
Section: Discussionsupporting
confidence: 90%
“…The results indicate that even in this region with the low magnesium content of the drinking water, prolonged dialysis did not deplete erythrocytes or bone of the excess levels of magnesium found in chronic renal failure. This finding over a period of 60 months corresponds with the previously reported results of short-term studies [10,22], In three patients studied, the decreased plasma and ultrafiltrable magnesium levels detected after dialysis returned to normal levels within 4 h. Whether the temporary fall in plasma magnesium concentration induced by dialysis ( fig. 1) is important in provoking an increased response from the para thyroid glands, thus exacerbating any tendency to metabolic bone disease, is not established.…”
Section: Discussionsupporting
confidence: 90%
“…In our patients undergoing hemodialysis with different Mg concentrations in the dialysate, the Mg serum levels paralleled the Mg level changes in the dialysis bath, thus confirming previous findings [11][12][13][14][15]. Although the changes of the Mg serum levels were statistically significant and were maintained for 6 months, they were not associated with any significant variation of the PTH serum levels.…”
Section: Discussionsupporting
confidence: 89%
“…Our investigation showed an inverse relationship be tween the erythrocyte Mg concentration and Ht in patients on chronic dialysis. This finding could account for the high concentrations found by other authors who probably ex amined only uremic patients with low Ht [1,[3][4][5][6], as also for the wide range of the erythrocyte Mg concentration found by Catto el al. [2], who probably studied patients having a broad range of Ht.…”
Section: Discussionmentioning
confidence: 53%
“…On the contrary, Johny el at. [3] pointed out that the high erythrocyte Mg levels in uremia are probably related to a marked resistance to cellular depletion despite low serum Mg levels, and Cano el al. [2] confirmed that low Mg fluid in prolonged dialysis did not deplete the erythrocytes of their Mg content.…”
Section: Discussionmentioning
confidence: 99%